The Neighborhood According to Women: Understanding Gendered Disorder Perceptions - Gaub, Janne E. (Crime & delinquency, 2021)
Women perceive higher rates of disorder in their neighborhood than males, though why remains unknown. We hypothesize that the differential role women play in neighborhood social life accounts for their higher disorder perceptions. To test this, we use the Seattle Neighborhoods and Crime Survey and fully interacted regressions with fixed effects for neighborhoods to determine if gendered disorder perceptions are a function of fear of crime, informal social control, and neighboring behaviors. Only the ability to identify strangers on the block predicts gendered disorder perceptions. Moreover, the fully interacted regressions account for most differences in gendered disorder perceptions. Our null findings have significant consequences for the supposed differential social role women have in their neighborhoods and fear of crime.